Pulmonary Artery Catheter Seemingly Entrapped in the Skull - S. M. Friedman; G. R. Rajan (Case Reports in Anesthesiology)
A pulmonary artery catheter is an important tool for the monitoring of hemodynamics in patients. Unfortunately, misplacement of a catheter tip may occur in the vasculature local to the intended placement. Misplacement of the catheter can be further complicated by entrapment at the unintended destination. We present a case of a misplaced and entrapped pulmonary artery catheter in a patient with worsening pulmonary disease. After multiple unsuccessful attempts to float the catheter, it was partially retracted and found to be stuck. Imaging showed the tip terminating in the right internal jugular vein at the level of the jugular foramen. It was initially suspected that the catheter had become looped, knotted, or otherwise entangled within the vasculature of the skull and surgical removal would be necessary. Before surgical removal was performed, it was instead determined that the catheter had become kinked and entrapped at the end of the introducer sheath, and noninvasive removal was accomplished by first removing the introducer sheath.